Una anècdota antiga i un lector eiximenià de Vicent Ferrer. - MARTÍNEZ ROMERO, TOMÀS (Scripta)
For a long time a rivalry between Francesc Eiximenis and Vicent Ferrer has been theorised due to certain actions and divergences in their thinking. This image is sometimes the outcome of popular beliefs built on long-standing traditions. The famous anecdote about the saint's "vanity" when entering València while being welcomed by a roaring crowd is part of the aforementioned tradition. Nevertheless, a critical review elicits many doubts about the historicity of this fact and the extent of Eiximenis and Ferrer's personal and ideological differences. Proof of this is the activity of a Vicentine sermons reader, who noted the similarities between these and some chapters of Primer del Crestià, beyond just common locations.